Chronic probiotic supplementation with or without glutamine does not influence the eHsp72 response to a multi-day ultra-endurance exercise event - Marshall, H.; Chrismas, B. C. R.; Suckling, C. A.; Roberts, J. D.; Foster, J.; Taylor, L. (Applied Physiology, Nutrition, and Metabolism, 2017)
Probiotic and glutamine supplementation increases tissue Hsp72, but their influence on extracellular Hsp72 (eHsp72) has not been investigated. The aim of this study was to investigate the effect of chronic probiotic supplementation, with or without glutamine, on eHsp72 concentration before and after an ultramarathon. Thirty-two participants were split into 3 independent groups, where they ingested probiotic capsules (PRO; n = 11), probiotic + glutamine powder (PGLn; n = 10), or no supplementation (CON; n = 11), over a 12-week period prior to commencement of the Marathon des Sables (MDS). eHsp72 concentration in the plasma was measured at baseline, 7 days pre-race, 6-8 h post-race, and 7 days post-race. The MDS increased eHsp72 concentrations by 124% (F[1,3] = 22.716, p < 0.001), but there was no difference in the response between groups. Additionally, PRO or PGLn supplementation did not modify pre- or post-MDS eHsp72 concentrations compared with CON (p > 0.05). In conclusion, the MDS caused a substantial increase in eHsp72 concentration, indicating high levels of systemic stress. However, chronic PRO or PGLn supplementation did not affect eHsp72 compared with control pre- or post-MDS. Given the role of eHsp72 in immune activation, the commercially available supplements used in this study are unlikely to influence this cascade.